2016
DOI: 10.18632/oncotarget.8481
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of skeletal growth of human prostate cancer by the combination of docetaxel and BKM1644: an aminobisphosphonate derivative

Abstract: Bone metastasis is a major cause of prostate cancer (PCa) morbidity and mortality. Despite some success in transiently controlling clinical symptoms with docetaxel-based therapy, PCa patients become docetaxel-resistant and inevitably progress with no cure. We synthesized an acyl-tyrosine bisphosphonate amide derivative, BKM1644, with the intent of targeting bone metastatic PCa and enhancing docetaxel's efficacy. BKM1644 exhibits potent anti-cancer activity in the NCI-60 panel and effectively inhibits the proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…Docetaxel treatment also suppressed p-CREB expression ( p < 0.001), with no significant effects on the levels of DRD2 or AR. Interestingly, survivin was slightly elevated in the tissues treated with docetaxel, an effect we have observed previously (31). The combination treatment resulted in increased expression of DRD2 ( p = 0.02) and decreased level of p-CREB ( p = 0.001) in bone tumors.…”
Section: Resultssupporting
confidence: 82%
“…Docetaxel treatment also suppressed p-CREB expression ( p < 0.001), with no significant effects on the levels of DRD2 or AR. Interestingly, survivin was slightly elevated in the tissues treated with docetaxel, an effect we have observed previously (31). The combination treatment resulted in increased expression of DRD2 ( p = 0.02) and decreased level of p-CREB ( p = 0.001) in bone tumors.…”
Section: Resultssupporting
confidence: 82%
“…Previously, we provided the first evidence indicating a positive correlation between survivin expression and clinical PCa bone metastasis, an observation supported by other studies [10][11][12]. We further showed that inhibition of survivin by small molecules or natural compounds could sensitize PCa cells to docetaxel treatment, resulting a synergistic suppression of tumor growth in mouse skeletons [13,14]. These results indicate that targeting survivin is a promising strategy to overcome therapeutic resistance and treat PCa bone metastasis.…”
Section: Introductionsupporting
confidence: 79%
“…Overexpression of survivin has been associated with clinical PCa bone metastasis [11,12]. In previous studies, we observed an increase in survivin expression following docetaxel treatment, and inhibition of survivin antagonized this inductive effect of docetaxel and sensitized PCa cells to chemotherapy [13,14]. These results indicate that survivin-targeted strategy could be a promising approach to overcome docetaxel chemoresistance and treat PCa bone metastasis.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Amino-bisphosphonate derivatives are another group of novel small-molecules, designed for targeting bone metastatic prostate cancer. These compounds have been shown to effectively inhibit tumor growth in bone, reduce prostate-specific antigens and improve bone structure in animal studies (Gera et al , 2008; Seo et al , 2008; Sh. Zhang et al , 2016).…”
Section: Introductionmentioning
confidence: 99%